An Analysis on Grammatical Errors in Students' Recount Texts: A Case Study on the Second Grade Students Faculty of Letters Indraprasta PGRI University - Sugianti Somba (Journal of English Language and Culture, 2018)
This study aims to analyze and classify what types of mistakes made by learners (in this case the second grade students of Indraprasta University PGRI) in applying the simple past tense in the text of recount text. The errors are defined according to Mariusz Trawinski's theory. In addition, this study aims to obtain percentage of each type of mistakes made by learners, as well as to uncover the most dominant mistakes made by learners in using the simple past tense in the text recount. The method used in this research is descriptive qualitative method, while the general pattern or research design used by the researcher is a case study. Furthermore, the authors chose the second level of students who numbered 25 people as subjects in this study. The data in this research is obtained through the test of making recounts to the students. The result of the error analysis process is that learners perform three types of errors which are regular verb, irregular verbs, and auxiliary verbs. It is seen from the percentage of each type of error, the auxiliary verb is the most commonly performed error type with a percentage of 42.23%. Furthermore, errors in irregular verb is 33.90%, whereas the type of regular verb error is  29.87% of the total errors made by the learner. And from the side of the taxonomy of surface tactics or surface strategy taxonomy, errors in regular verb, irregular verb, and to be auxiliary consist of misformation, misordering, omission, and addition error. The highest error on auxiliary verb is misformation. The highest error on irregular verb is misformation. And the highest error in regular verb is omission. This shows that the use of simple past tense in writing recount text is still difficult to understand the students of the second grade of PGRI Indraprasta University. Keywords: simple past, recount texts